Fighting chance global trends and shocks in the national security environment - Arnas, Neyla (Potomac Books, 2009)
Compiled to meet the challenges of a rapidly changing security environment, this important collection grew out of an innovative Department of Defense (DOD) workshop. The book's purpose is to examine strategic trends, their defense relevance, how they may overlap to produce strategic "shocks"--Such as the launch of Sputnik and the fall of the Berlin Wall-and how the United States might prepare for such events to mitigate risks and capitalize on opportunities. From a broad range of backgrounds, distinguished authors work from the premise of the six trend categories identified by DOD: conflict; demographics; economy; environment; culture, identity, and governance; and science and technology. Another group of regional experts considers these six categories in the context of their respective regions: Africa, China, Europe and the North Atlantic Treaty Organization, Russia and Eurasia, South Asia, and Latin America. Looking insightfully at broad trends, Fighting Chance goes well beyond the obvious dangers they might pose in order to warn of future perils-and to suggest opportunities. (Barnes & Noble)